1960
DOI: 10.1002/jsfa.2740110802
|View full text |Cite
|
Sign up to set email alerts
|

Pilot‐plant studies on the preparation of crude papain from raw papaya

Abstract: The results are presented of an investigation of the yield and total solids content of the latex obtained in successive tappings of papaya fruit and of the yield and activity of the crude papain obtained from the latex samples by sun-and vacuum-drying. The effect of the addition of metabisulphite, with and without thymol, on the activity of th'e dried products is described. IntroductionStudies on the preparation of papain have been conducted by several w,orker~,l-~ but little information is available in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1969
1969
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Umbrella-like devices are fixed around the trunks to collect the exuded latex, which is then dried. The following diverse recommendations concerning optimum fruit age occur in the literature: the tapping can commence when the fruits are (i) 4 inch in diameter or when the trees are 9-12 months ~l d ;~-~ (ii) 3 months after fruit set;?, 8 (iii) 2 weeks before ripening;g, 10 (iv) fruits one-half to three-quarters deve1oped;ll (v) full size green fruits;l (vi) the proteolytic activity is highest in 5-month-old fruit. 12 Preliminary experiments at CITA indicated that there is considerable inter-fruit and inter-tree variation.…”
Section: Introductionmentioning
confidence: 99%
“…Umbrella-like devices are fixed around the trunks to collect the exuded latex, which is then dried. The following diverse recommendations concerning optimum fruit age occur in the literature: the tapping can commence when the fruits are (i) 4 inch in diameter or when the trees are 9-12 months ~l d ;~-~ (ii) 3 months after fruit set;?, 8 (iii) 2 weeks before ripening;g, 10 (iv) fruits one-half to three-quarters deve1oped;ll (v) full size green fruits;l (vi) the proteolytic activity is highest in 5-month-old fruit. 12 Preliminary experiments at CITA indicated that there is considerable inter-fruit and inter-tree variation.…”
Section: Introductionmentioning
confidence: 99%